2014
DOI: 10.2215/cjn.04140414
|View full text |Cite
|
Sign up to set email alerts
|

X-Linked Alport Syndrome Caused by Splicing Mutations in COL4A5

Abstract: Background and objectives X-linked Alport syndrome is caused by mutations in the COL4A5 gene. Although many COL4A5 mutations have been detected, the mutation detection rate has been unsatisfactory. Some men with X-linked Alport syndrome show a relatively mild phenotype, but molecular basis investigations have rarely been conducted to clarify the underlying mechanism.Design, setting, participants, & measurements In total, 152 patients with X-linked Alport syndrome who were suspected of having Alport syndrome th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 27 publications
4
44
0
Order By: Relevance
“…On the other hand, mild renal disease in a male, despite carrying a splice region variant that causes a truncation, has also been described before. Nozu et al demonstrated the presence of wild type and abnormal transcripts in the kidney of an affected male with a splice region variant in COL4A5 that causes a truncation [21]. Our findings also suggest that incomplete splicing abnormalities might occur in the kidney and lead to a variable phenotype.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…On the other hand, mild renal disease in a male, despite carrying a splice region variant that causes a truncation, has also been described before. Nozu et al demonstrated the presence of wild type and abnormal transcripts in the kidney of an affected male with a splice region variant in COL4A5 that causes a truncation [21]. Our findings also suggest that incomplete splicing abnormalities might occur in the kidney and lead to a variable phenotype.…”
Section: Discussionsupporting
confidence: 65%
“…Although other groups have reported using RNA extracted from hair follicles to assay COL4A5 expression and/or mRNA splicing by RT-PCR [2123], we were unable to obtain enough intact RNA to determine the extent to which normal splicing of exon 25 occurs in vivo . However, if a low frequency of exon 25 retention does occur in vivo , it could partly explain the differences in disease severity among the affected males in this family (e.g., individual 3 compared to individuals 3222 and 3227), and it may also partly explain differences in phenotype between affected females (e.g., individual 3223 who has preserved renal function and her daughter, individual 3226, who has CKD stage 3).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…; Nozu et al. ), although dominant negative effects of the mutated allele cannot be excluded. Our results highlight the importance of characterizing aberrant transcripts for accurate prognosis of this patient and hereditary disorders in general, with potentially important implications for their management.…”
Section: Discussionmentioning
confidence: 99%
“…22 The milder phenotype in men with XLAS is currently defined by the following five patterns: (1) missense variants in COL4A5; 4-6 (2); in-frame variants in COL4A5; 4,6 (3) somatic mosaic variants in COL4A5; 7,19-21 (4) α5(IV)-positive expression in the glomerulus; 6 and (5) aberrant splicing variants in COL4A5, leading to both normal and abnormal mRNAs. 22 In this study, we reported four cases with milder phenotypes: two with splice site variants (ID14 and 28) and two with missense variants (ID52 and 252). These variant types could contribute to a modulation of the phenotype.…”
Section: Discussionmentioning
confidence: 99%